FOLLICULAR THYROGLOBULIN ANTAGONIZES THE ACTION OF TSH AND REGULATES THE EXPRESSION AND LOCALIZATION OF THE NOVEL IODIDE TRANSPORTER SLC26A7 - Kiriya, Mitsuo; Kawashima, Akira; Fujiwara, Yoko; Kondo, Tetsuo; Suzuki, Koichi (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES Thyroglobulin (Tg) stored in the follicular lumen serves as a potent negative feedback regulator of follicular function that controls the expression of thyroid-specific genes. Recently, SLC26A7, a novel gene responsible for congenital hypothyroidism, was identified as an apical iodide transporter of thyrocytes. In this study, we examined the effects of TSH and follicular Tg on the expression and localization of SLC26A7. METHODOLOGY Rat thyroid FRTL-5 cells were stimulated by TSH or follicular concentrations of Tg. SLC26A7 mRNA and protein expression levels were evaluated using real-time PCR and Western blotting, respectively. Changes in subcellular localization of SLC26A7 in FRTL-5 cells and rat thyroid tissue sections were analyzed using confocal laser scanning microscopy. RESULTS TSH suppressed both mRNA and protein levels of SLC26A7, while it translocated SLC26A7 from the perinuclear area to the cell membrane. Tg also suppressed mRNA and protein levels of SLC26A7. However, Tg inhibited the ability of TSH to induce the plasma membrane localization of SLC26A7. In rat thyroid sections, SLC26A7 localization was inversely correlated with that of follicular Tg. CONCLUSION We have demonstrated that both TSH and follicular Tg suppressed the expression of SLC26A7. However, Tg inhibited the action of TSH to localize SLC26A7 to the plasma membrane both in vitro and in vivo. These results corroborate our hypothesis that the function of individual follicles is strongly regulated by the level of Tg accumulated in the follicular lumen.